2004
DOI: 10.1590/s1516-89132004000100013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apple pomace based reconstituted feed in rats after solid state fermentation and ethanol recovery

Abstract: To utilize apple pomace in an economical and effective way, a feed was developed by solid state fermentation (SSF) using sequential interactive co-culture of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The co-culture of Candida utilis and Aspergillus niger increased the protein content of dried and pectin-extracted apple pomace to 20% and 17%, respectively, under SSF conditions [5]. The combination of fermented apple pomace with standard feed in the ratio of 1:1 was found to be acceptable during animal experiment with rat model [6]. The apple pomace based feed had also been evaluated successfully in poultry, when mixed with standard poultry feed in 1:1.…”
Section: Introductionmentioning
confidence: 94%
“…The co-culture of Candida utilis and Aspergillus niger increased the protein content of dried and pectin-extracted apple pomace to 20% and 17%, respectively, under SSF conditions [5]. The combination of fermented apple pomace with standard feed in the ratio of 1:1 was found to be acceptable during animal experiment with rat model [6]. The apple pomace based feed had also been evaluated successfully in poultry, when mixed with standard poultry feed in 1:1.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies demonstrated the use of AP for the production of protein-enriched feeds [13,175,36,7,171]. Bhalla and Joshi [13] employed the fungi Trichoderma viride and A. niger and the yeasts S. cerevisiae and C. utilis combined for the protein enrichment of AP in SSF and SmF.…”
Section: Protein Enrichmentmentioning
confidence: 99%
“…The presence of lignin and cellulose/hemicellulose acts as natural inducers, and most of these residues are rich in sugar, promoting better fungal growth and thus making the process more economical especially for the cellulo-and ligninolytic enzymes [33,132,38]. AP has been used for the production of organic acids [153,39,40,48], aroma compounds [18,168,120], bioethanol [128,129,135], enzymes [63,41,42,43,47,103,175], edible mushrooms [182,54,, edible fibers [72,114,135], pectin recovery [149], natural antioxidants [65,6], protein enriched animal feed [13,36,7,150,171], and insect diets [71] among others. AP has also been considered for environmental applications, such as textile dye removal [142] and as heavy metal absorbent [126].…”
Section: Introductionmentioning
confidence: 99%
“…Trace amounts of phenolic compounds suffice to give apple-derived products their distinctive sourness and astringency, which usually enhance their flavor, such as that of cider (Downing 1989;Devrajan et al 2004). Apple pomace represents 20 to 40% of the raw material and it is the by-product of apple juice processing.…”
Section: Introductionmentioning
confidence: 99%